Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) pada Perusahaan Pertambangan - Sembiring, Grada (Seminar Nasional Manajemen, 2026)
This study aims to analyze the effect of job satisfaction and organizational commitment on Organizational Citizenship Behavior (OCB) among employees of a private mining company in Indonesia. OCB refers to voluntary employee behavior that exceeds formal job responsibilities and contributes to organizational effectiveness, particularly in industries with high operational demands. This research employs a quantitative approach with an associative research design. Data were collected through structured questionnaires distributed to all employees totaling 60 respondents using a saturated sampling technique. Multiple linear regression analysis was applied to examine the partial and simultaneous effects of job satisfaction and organizational commitment on OCB. The results indicate that job satisfaction and organizational commitment have a positive and significant effect on OCB, with organizational commitment showing a more dominant influence. These findings suggest that improving employee satisfaction and strengthening organizational commitment are essential strategies for encouraging extra-role behavior and enhancing organizational performance in the mining sector.